Draft Annual Plan 1979-80 (In 4 Volumes) Vol. IV Haryana State - Planning Commission (Planning Commission, 1979)
A sum of Rs. 52.00 lakhs is proposed for the year 1979-80 for constructing 60 additional rooms, acquiring 20 rented primary and Middle school buildings and constructing 250 new rooms, in buildings Where existing ones were badly damaged by the un-precedented floods in the State during 1977-78 & 1978-79.
Planning Department, Government of Haryana